Simulation exercises in police education, why and how? A teacher's perspective - David Sjöberg (International Journal for Research in Vocational Education and Training (IJRVET), 2024)
Context: This study is about the teaching method of simulation exercises and is set in a police education context. Simulation exercises are a central part of Swedish police education, and therefore it is of interest to explore how they are used, and for what purpose, by investigating police teachers' perceptions of this teaching and learning method. Police teachers are police officers who work as teachers at a police education unit on contracts lasting a few years, but which can be extended, and they usually lack any formal pedagogical training. Approach: In this study, the exploration of the use of simulation exercises was conducted through an inductive approach which included semi-structured interviews with 12 police teachers. The analysis was carried out in several steps. To promote impartiality in the initial data analysis the researcher first stayed close to the data and connection with the findings of previous studies was only considered in the latter stages of this analytic process. Findings: The findings show that the police teachers perceive that the overall purpose of simulation exercises is for students to apply specific content taught in courses, both physical techniques and methods, and more theoretical knowledge, in the fluid context of scenarios relevant to police work. The results also show that the teachers are aware that the purpose of the exercises is stated in the planning documents, but because they inherit the designs from previous teachers, they may not be aware of the underlying details of it or what is to be achieved in the scenario. The findings also demonstrate that the teachers learn the craft of designing and performing simulation exercises and develop their roles as teachers through an informal workplace learning process that involves tacit knowledge developed through working together, and by talking to and observing each other. Conclusion: The paper contributes to the field of simulation exercises in vocational (higher) education in that the findings can provide educated arguments for the need for scholarly discussions on simulation exercises as a pedagogical tool that supports student learning, as well as arguments for why formal pedagogically-oriented continuing education on the design and implementation of simulation exercises where learning is in the foreground may be needed to support police teachers' professional development.
Keywords: 330; Simulation; Education and Training Opportunity; Police Training; Learning Activities; Vocational Education and Training; Vocational Preparation; VET